2006
DOI: 10.1051/forest:2006048
|View full text |Cite
|
Sign up to set email alerts
|

Age trends in genotypic variation of wood density and its intra-ring components in young poplar hybrid crosses

Abstract: -Age related dynamics of genotypic, phenotypic, and environmental variation, clonal repeatability, and genotypic correlations for wood density and its intra-ring components were analyzed in four poplar hybrid crosses, Populus deltoidesˆP. nigra, P. trichocarpaˆP. deltoides, P. maximowicziiˆP. balsamifera, and P. balsamiferaˆP. nigra, as well as P. deltoides. Using X-ray densitometry, measurements were taken on increment cores sampled in four clonal trials at 10 and 12 years of age from ramets of 19 clones. Woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(33 reference statements)
3
9
0
1
Order By: Relevance
“…Because of mismatching between test locations and deployment zones, G  E interaction, if improperly accounted for, can result in bias of estimates and thus in decrease of genetic gain. The hybrid  site interaction for dry biomass production was found to be significant in our previous study [44,42] while it was not significant in other study in which only two sites and fewer hybrids were investigated [43]. The interaction may be related to differences between hybrids in adaptability to unfavourable or stressful site conditions.…”
Section: 4mentioning
confidence: 48%
See 1 more Smart Citation
“…Because of mismatching between test locations and deployment zones, G  E interaction, if improperly accounted for, can result in bias of estimates and thus in decrease of genetic gain. The hybrid  site interaction for dry biomass production was found to be significant in our previous study [44,42] while it was not significant in other study in which only two sites and fewer hybrids were investigated [43]. The interaction may be related to differences between hybrids in adaptability to unfavourable or stressful site conditions.…”
Section: 4mentioning
confidence: 48%
“…Tree conditions and survival rates in the Dubrava site were lower, possibly due to damage to tree stems by rodents. Strongly significant site effects were obtained for growth traits, stem volume and dry fibre biomass in previous studies of hybrid poplars tested in southern Quebec in Canada on four sites [44,42] and on eight sites [50]. The large site effect was found in yield, on the most productive site being as high as 22.4 m 3 ha À1 y À1 and on the poorest site as low as 1.1 m 3 ha À1 year À1 [50].…”
Section: Variation Among Sitesmentioning
confidence: 59%
“…Nevertheless, variations in wood density can be difficult to understand, since this complex trait is not a single property but a complex of several intra-ring components, including minimum and maximum wood densities, early and late wood densities, proportion of latewood etc (Pliura et al, 2006). Another important wood property is the spiral grain, a term applied to the helical orientation of the tracheids in a tree stem.…”
Section: Introductionmentioning
confidence: 99%
“…Age-age correlations of wood density need to be explored for fast growing elite families to study possible undue effect on growth traits. In the literature, strong age-age correlations were reported for wood density in hybrid poplar clones (Pliura et al, 2006). Wu et al (2007) reported stable wood density values from ages 11-15 to rotation-age in Pinus radiata, which is encouraging.…”
Section: Implications For Improvement Of Wood Densitymentioning
confidence: 84%